Good guy in bad company: How STRNs convert PP2A into an oncoprotein - Kurppa Kari J; Westermarck Jukka (United States, 2022)
Certain Protein Phosphatase 2A (PP2A) complexes are human tumor suppressors. In contrast, a paper in this issue of Cancer Cell and two other recent studies demonstrate that PP2A-STRN3/4 complexes inactivate Hippo tumor suppressor pathway, resulting in YAP activation and tumorigenesis. Furthermore, this new oncogenic phosphatase mechanism may be druggable